The Legacy of the Moral Tale : Children's Literature and the English Novel, 1744-1859 - Fleming, Patrick C. (Book collections on Project MUSE., 2016)
The moral tale was foremost among the new genres of children's literature that emerged in Britain during the late eighteenth and early nineteenth centuries. Written expressly to impart moral lessons to their young readers, such tales had a profound impact on the generation we now know as the Victorians. In this original and discerning study, Patrick Fleming traces the rise and subsequent impact of the moral tale through the works of representative authors like Thomas Day, Maria Edgeworth, and Charles Dickens, who through Oliver Twist and later writings developed his own brand of experiential didacticism which clearly had roots in the moral tales he read as a child. Scholars studying Victorians' childhood reading have typically emphasized fairy tales and eighteenth-century novels rather than works especially written for children, while children's literature scholars have focused on the "Golden Age," which began around 1860 and is epitomized by such works as Lewis Carroll's Alice' Adventures in Wonderland. However, as The Legacy of the Moral Tale makes clear, children's literature began long before the Golden Age, and the moral tale was prominent among the genres the Victorians remembered. In revealing this long-overlooked connection, the book expands our understanding of the history of the novel and highlights the moral instruction to which nineteen-century readers were accustomed. -- from back cover.